Morpho-histochemical characterization of the salivary glands of semi-engorged Amblyomma triste (Koch, 1844) (Acari: Ixodidae) female ticks. Issue 2 (June 2015) - de Oliveira, Patrícia Rosa; Furquim, Karim Christina Scopinho; Bechara, Gervásio Henrique; Camargo-Mathias, Maria Izabel
Abstract: This study presents the morphological and physiological characterization of the salivary glands of semi-engorged Amblyomma triste females. Unfed individuals were placed on New Zealand White rabbits for feeding and the females, after 4 days, were collected, dissected and the salivary glands were submitted to the application of histological (hematoxylin–eosin technique) and histochemical tests for the detection of protein (bromophenol blue technique, polysaccharides (periodic acid–Schiff technique), lipid (Nile blue technique) and calcium (von Kossa technique). The histological results show that the glandular tissue is composed by a system of ducts and three types of acini (I, II and III). The acini I are formed by a large central cell surrounded by several smaller agranular peripheral cells. Acini II are formed by cellsa, c1, c2, c3 andc5, which are full of secretion granules. Acini III are constituted by cellsd, e andf ; the former two contain secretion granules, the latter is agranular. The glandular histochemical composition was also verified. Data obtained here will certainly help in the understanding of the cellular morphology and of the general physiology of these organs in this specie, providing important information for the creation of scientific bases which will contribute for the development of more specific and efficient methods of control.